PERANCANGAN SISTEM INFORMASI PENDAFTARAN SISWA BARU PADA TAMAN KANAK - ANAK ANNURIYAH BERBASIS WEB JAKARTA - Setiawan, Setiawan; Fadli, Ahmad; Subagiyo, Subagiyo; Farida, Kania (POLITEKNIK LP3I JAKARTA, 2020)
Annuriyah Kindergarten is a private institution engaged in education located in East Kalibata, South Jakarta. This First Kindergarten still needs the right data processing in order to create time efficiency and data accuracy that can support operational, management and decision-making processes properly and accurately. The process of accepting new students in this Kindergarten is still not using computerization. Prospective students in the registration process must enter data by writing a form, after the data is written in the registration form, then the data is entered into the computer using Microsoft Excel software and has not used an information system. Keywords: Student Registration, Students, Kindergarten, Excel